1995
DOI: 10.1021/cm00055a022
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Iron Carbide in Carbon Nanocapsules

Abstract: Whiskers of iron carbide encased in carbon shells have been prepared from iron (I1) phthalocyanine. Solid FePc is oxygenated and then thermally treated under H2 flow. With proper control of conditions, Fe3C free from metallic iron can be synthesized. The product was characterized with the help of Mossbauer effect spectroscopy, X-ray diffraction, X-ray absorption, and transmission electron microscopy. The iron carbide whiskers range in length from 300 to 500 nm, and their widths are approximately 100 nm. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
6
19
0
1
Order By: Relevance
“…It is essential to know the mechanism of the formation of the nanocapsules in order to be able to control their diameter and thickness of the carbon coatings. In our earlier research [1], we showed that controlled pyrolysis of flat layered iron phthalocyanine (FePc) [2] can be used to prepare carbon nanotubes. Since the oxygenation of the FePc complex is the key step in the synthesis, there is a great interest in the exploration of the interaction of oxygen with FePc.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to know the mechanism of the formation of the nanocapsules in order to be able to control their diameter and thickness of the carbon coatings. In our earlier research [1], we showed that controlled pyrolysis of flat layered iron phthalocyanine (FePc) [2] can be used to prepare carbon nanotubes. Since the oxygenation of the FePc complex is the key step in the synthesis, there is a great interest in the exploration of the interaction of oxygen with FePc.…”
Section: Introductionmentioning
confidence: 99%
“…As for example pyrolysis of metaloorganic compounds was proposed. In fact this method yielded carbon-encapsulated magnetic nanoparticles; however, it required the starting reactants of high complexity (and therefore the high cost) and long reaction times even up to several days [14,15]. Another routes involve two-step processes in which the carbon coatings were deposited onto previously prepared metal nanoparticles with specified diameters [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…В работе [8] карбид железа, инкапсулированный в углеродную оболочку, синтезировали пиролизом FePc в потоке H 2 при 300−400…”
Section: Introductionunclassified